2010
DOI: 10.1158/1541-7786.mcr-09-0453
|View full text |Cite
|
Sign up to set email alerts
|

EphB4 Promotes Site-Specific Metastatic Tumor Cell Dissemination by Interacting with Endothelial Cell–Expressed EphrinB2

Abstract: The tyrosine kinase receptor EphB4 interacts with its ephrinB2 ligand to act as a bidirectional signaling system that mediates adhesion, migration, and guidance by controlling attractive and repulsive activities. Recent findings have shown that hematopoietic cells expressing EphB4 exert adhesive functions towards endothelial cells expressing ephrinB2. We therefore hypothesized that EphB4/ephrinB2 interactions may be involved in the preferential adhesion of EphB4-expressing tumor cells to ephrinB2-expressing en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 53 publications
1
30
0
Order By: Relevance
“…However, ephrin-B2 is also present in tumours, expressed primarily on the endothelial cells of the tumour vasculature and by fibroblasts in the surrounding prostate tumour stroma [13,14]. Several groups have shown that endothelial cell ephrin-B2 plays a key role in regulating angiogenesis and lymphangiogenesis, an important element in supporting tumour growth and for arresting cells during site-specific metastatic dissemination [15][16][17]. Thus, collectively these studies suggest a fine balance and tight regulation of EphB4-ephrin-B2 interaction exists that is critical to the promotion or suppression of tumour growth and spread.…”
Section: Introductionmentioning
confidence: 99%
“…However, ephrin-B2 is also present in tumours, expressed primarily on the endothelial cells of the tumour vasculature and by fibroblasts in the surrounding prostate tumour stroma [13,14]. Several groups have shown that endothelial cell ephrin-B2 plays a key role in regulating angiogenesis and lymphangiogenesis, an important element in supporting tumour growth and for arresting cells during site-specific metastatic dissemination [15][16][17]. Thus, collectively these studies suggest a fine balance and tight regulation of EphB4-ephrin-B2 interaction exists that is critical to the promotion or suppression of tumour growth and spread.…”
Section: Introductionmentioning
confidence: 99%
“…We believe this signaling would be further enhanced in an environment, such as bone marrow, where stroma expresses ephrinB2. Previous work has shown that tumor cells with EPHB4 expression can interact with ephrinB2 on stroma and vasculature to promote growth 30 and confer resistance to therapy. 31 Disrupting EPHB4/ephrinB2 interaction may, therefore, be a strategy to overcome treatment resistance.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, EPH receptors and their ligands can regulate stem/progenitor cell proliferation in adult tissues as well as tumor progression; this is a relevant function of EPH receptors in the context of oncology[47]. Moreover, EPH receptors can promote the dissemination of tumor cells by guiding amoeboid movement toward EPH ligands that are expressed on endothelial cells at sites of future metastatic tumor formation[48],[49]. Furthermore, natural killer cells and monocytes triggered a larger reduction in xenograft tumor volume when EPHA2 antibodies were present, suggesting that the immune system can also contribute to the function of EPH receptors in cancer[50].…”
Section: Eph Receptorsmentioning
confidence: 99%